2017
DOI: 10.5194/hess-2017-406
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Shallow water table effects on water, sediment and pesticide transport in vegetative filter strips: Part B. model coupling, application, factor importance and uncertainty

Abstract: Abstract. Vegetative filter strips are often used for protecting surface waters from pollution transferred by surface runoff in agricultural watersheds. In Europe, they are often prescribed along the stream banks, where a seasonal shallow water table (WT) could decrease the buffer zone efficiency. In spite of this potentially important effect, there are no systematic experimental or theoretical studies on the effect of this soil boundary condition on the VFS efficiency. In the companion paper, we developed a p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Data available on the variations in water table level and pesticide concentrations in the shallow groundwater under the grassed strip during an artificial runoff event also highlights a rapid decrease in peak infiltrated pesticide concentrations. This data set was used to test slope‐scale models (Carluer et al, 2017; Gatel et al, 2020; Lauvernet & Munoz‐Carpena, 2018).…”
Section: Site Description Measured Data and Main Resultsmentioning
confidence: 99%
“…Data available on the variations in water table level and pesticide concentrations in the shallow groundwater under the grassed strip during an artificial runoff event also highlights a rapid decrease in peak infiltrated pesticide concentrations. This data set was used to test slope‐scale models (Carluer et al, 2017; Gatel et al, 2020; Lauvernet & Munoz‐Carpena, 2018).…”
Section: Site Description Measured Data and Main Resultsmentioning
confidence: 99%
“…Muñoz‐Carpena et al (2018) showed that good results can be obtained when the slope of the wetting front is taken as α = 0 across a wide range of soil types, and extended the approach to include a surface water budget to calculate the infiltration rate, excess rainfall, θ redistribution profiles, and the wetting front position at each time step for initially non‐ponded soil under unsteady r . Lauvernet and Muñoz‐Carpena (2018) coupled SWINGO with a widely used vegetative filter strip and riparian buffer design model, VFSMOD (Muñoz‐Carpena et al, 1999; Muñoz‐Carpena and Parsons, 2004), that contains overland flow and transport processes, and Fox et al (2018) experimentally tested the coupled model under controlled laboratory conditions.…”
Section: Modeling Macropore Flowmentioning
confidence: 99%
“…It is also dependent on a balance between constructive and destructive processes and, consequently, potentially influenced by changes in the relationship between the soil and the flora and fauna community, as well as by changes in external conditions such as climatic variations (Beven and Germann, 1982). In addition, riparian areas, especially those located in lowlands, may be strongly influenced by a seasonal shallow water table (SWT) (Fox et al, 2018; Lauvernet and Muñoz‐Carpena, 2018; Muñoz‐Carpena et al, 2018). A system with a SWT will have higher soil moisture and a lower infiltration capacity, resulting in a higher overland runoff transport rate and greater MF activation that ultimately can reduce riparian buffering efficiency.…”
mentioning
confidence: 99%
“…Similarly, slopes can be determined through field measurements or by using a GIS. Saturated hydraulic conductivity is a key parameter of the model and is often the most influential, together with water table depth depending on the hydraulic loading (Muñoz-Carpena et al, 2010;Lauvernet and Muñoz-Carpena, submitted). It is therefore important to assign a value as representative as possible of the real conductivity value.…”
Section: Ii3 Buffer Zone Efficiency Modelling Approachmentioning
confidence: 99%